Actin-mediated microglial chemotaxis via G-protein coupled purinergic receptor in alzheimer's disease - Das, Rashmi; Chinnathambi, Subashchandrabose (Neuroscience, 2020)
Alzheimer's disease (AD) is a neurodegenerative disease mainly associated with aging, oxidative stress and genetic mutations. There are two pathological proteins involved in AD; Amyloid-beta peptide and microtubule-associated protein Tau (MAPT). The beta- and gamma-secretase enzyme cleaves the Amyloid precursor protein, which results in the formation of extracellular plaques in brain. While, Tau undergoes hyperphosphorylation and other post-translational modifications (PTMs), which eventually generates Tau oligomers, and intracellular neurofibrillary tangles (NFTs) in neurons. Moreover, the brain-resident glia and infiltrated macrophages elevate the level of CNS inflammation, which trigger the oxidative damage of neuronal circuits by reactive oxygen species (ROS) and Nitric oxide (NO). Microglia is the primary immune cell in the CNS, which is continuously surveilling the neuronal synapses and pathogen invasion. Microglia in the resting state is called `Ramified', which possess long surveilling extensions with a small cell body. But, upon activation, microglia retracts the cellular extensions and transform into round migratory cells, called as `Amoeboid' state. Activated microglia undergoes actin remodeling by forming lamellipodia and filopodia, which directs the migratory axis while podosomes formed are involved in extracellular matrix degradation for invasion. Protein-aggregates in malfunctioning synapses and in CNS milieu can be detected by microglia, which results in its activation and migration. Subsequently, the phagocytosis of synapses leads to the inflammatory burst and memory loss. The extracellular nucleotides released from damaged neurons and the cytokine-chemokine gradients allow the neighboring microglia and macrophages to migrate-infiltrate at the site of neuronal-damage. The ionotropic (P2XR) and metabotropic (P2YR) purinergic receptor recognize extracellular ATP/ADP, which propagates through the intracellular calcium signaling, chemotaxis, phagocytosis and inflammation. The P2Y receptors give `find me' or `eat me' signals to microglia to either migrate or phagocytose cellular debris. Further, the actin cytoskeleton helps microglia to mediate directed chemotaxis and neuronal repair during neurodegeneration. Hence, we aim to emphasize the connection between purinergic signaling and actin-driven mechanical movements of microglia for migration and inflammation in AD. (C) 2020 IBRO. Published by Elsevier Ltd. All rights reserved.
Keywords: actin remodeling; Alzheimer's disease; microglia; P2Y signaling; purinergic GPCRs; Tauopathy

Autophagic pathways to clear the tau aggregates in alzheimer's disease - Gorantla, Nalini Vijay; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2020)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin-proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.
Keywords: Alzheimer's disease; Chaperone-mediated autophagy; Lysosome-associated membrane proteins-2A; Macroautophagy; Neurofibrillary tangles; Tau; Tau degradation; Ubiquitin-proteasome system

Alpha-Linolenic acid inhibits Tau aggregation and modulates Tau conformation - Desale, Smita Eknath; Dubey, Tushar; Chinnathambi, Subashchandrabose (International Journal of Biological Macromolecules, 2021)
Alzheimer's disease is characterized by important patho-proteins, which being composed of Amyloid-beta, plaques and intracellular neurofibrillary tangles of Tau. Intrinsically disordered protein tau has several interacting partners, which are necessary for its normal functioning. Tau has been shown to interact with various proteins, nucleic acid, and lipids. alpha-Linolenic acid (ALA) a plant-based omega-3 fatty acid has been studied for its role as neuroprotective and beneficial fatty add in the brain. In this study, we are focusing on the ability of ALA to induce spontaneous assembly in tau protein. ALA inhibited the Tau aggregation as indicated by reduced ThS fluorescence kinetics, which indicates no aggregation of Tau. Similarly, SDS-PAGE analysis supported that ALA exposure inhibited the aggregation as no higher-order tau species were observed. Along with its ability to impede the aggregation of Tau, ALA also maintains a native random coiled structure, which was estimated by CD spectroscopy. Finally, TEM analysis showed that the formation of Tau fibrils was found to be discouraged by ALA. Hence, conclusion of the study suggested that ALA profoundly inhibited aggregation of Tau and maintained it's the random-coil structure. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: alpha-linolenic acid; Alzheimer's disease; Free fatty adds; Tau conformation; Tau fibrillization

Alpha-Linolenic acid modulates phagocytosis and endosomal pathways of extracellular Tau in microglia - Desale, Smita Eknath; Chinnathambi, Subashchandrabose (Cell Adhesion & Migration, 2021)
Microglia, the resident immune cells, were found to be activated to inflammatory phenotype in Alzheimer's disease (AD). The extracellular burden of amyloid-beta plaques and Tau seed fabricate the activation of microglia. The seeding effect of extracellular Tau species is an emerging aspect to study about Tauopathies in AD. Tau seeds enhance the propagation of disease along with its contribution to microglia-mediated inflammation. The excessive neuroinflammation cumulatively hampers phagocytic function of microglia reducing the clearance of extracellular protein aggregates. Omega-3 fatty acids, especially docosahexaenoic acid and eicosapentaenoic acid, are recognized to induce anti-inflammatory phenotype of microglia. In addition to increased cytokine production, omega-3 fatty acids enhance phagocytic receptors expression in microglia. In this study, we have observed the phagocytosis of extracellular Tau in the presence of alpha-linolenic acid (ALA). The increased phagocytosis of extracellular Tau monomer and aggregates have been observed upon ALA exposure to microglia cells. After internalization, the degradation status of Tau has been studied with early and late endosomal markers Rab5 and Rab7. Further, the lysosome-mediated degradation of internalized Tau was studied with LAMP-2A, a lysosome marker. The enhanced migratory ability in the presence of ALA could be beneficial for microglia to access the target and clear it. The increased migration of microglia was found to induce the microtubule-organizing center repolarization. The data indicate that the dietary fatty acids ALA could significantly enhance phagocytosis and intracellular degradation of internalized Tau. Our results suggest that microglia could be influenced to reduce extracellular Tau seed with dietary fatty acids.
Keywords: alpha-linolenic acid; endosomal markers; Fatty acids; MTOC repolarization; Phagocytosis; Tauopathy

Amyloid-beta-derived peptidomimetics inhibits tau aggregation - Gorantla, V. Nalini; Sunny, Lisni P.; Rajasekhar, Kolla; Nagaraju, Pramod G.; Priyadarshini, Poornima C. G.; Govindaraju, Thimmaiah; Chinnathambi, Subashchandrabose (ACS Omega, 2021)
The aggregation of tau protein is one of the hallmarks for Alzheimer's disease, resulting in neurodegeneration. The peptidomimetics strategy to prevent tau aggregation is more specific over other small molecules. In the present study, we analyzed the effect of amyloid-beta-derived peptidomimetics for inhibiting heparin-induced tau aggregation in vitro. These peptides and their derivatives were known to prevent aggregation of amyloid-beta. KLVFF is a hydrophobic sequence of the pentapeptide that prevented tau aggregation as observed by thioflavin S fluorescence, transmission electron microscopy, and circular dichroism spectroscopy. P4 and P5 also prevented assembly of tau into aggregates and formed short fibrils. The beta-sheet breaker LPFFD was however ineffective in preventing tau aggregation. The peptides further demonstrated reversal of tau-induced cytotoxicity in a dose-dependent manner. Our results suggested that these peptides can also be used to inhibit tau aggregation and also, toxicity induced by tau could be considered as potential molecules that have an effect on tau as well as amyloid-beta.

Autophagic pathways to clear the tau aggregates in alzheimer’s disease - vijay nalini, Gorantla; Chinnathambi, Subashchandrabose (Cellular and Molecular Neurobiology, 2021)
Tau is a microtubule-associated protein with an intrinsically unstructured conformation. Tau is subjected to several pathological post-translational modifications (PTMs), leading to its loss of interaction with microtubules and accumulation as neurofibrillary tangles (NFTs) in neurons. Tau aggregates impede functions of endoplasmic reticulum and mitochondria leading to the generation of oxidative stress and in turn amplifying the Tau aggregation. Tau is channelled to chaperones for folding into their native form, which otherwise causes its degradation and clearance. Cellular response triggers the activation of ubiquitin–proteasome system or autophagy to facilitate Tau degradation, based on the PTMs or mutations associated with Tau. Further, autophagy can be selective where Hsc70 interacts with Tau in monomeric, oligomeric and aggregated form and drives its clearance by chaperone-mediated autophagy pathway (CMA). Lysosome-associated membrane proteins-2A (LAMP-2A) is the key player of CMA that recognises Hsc70-Tau complex and triggers the downstream cascade. Thus, it becomes challenging for mutant Tau to be cleared by CMA as it loses its affinity for Hsc70 and LAMP-2A. In such a scenario, Tau might be degraded by macroautophagy otherwise sequestered by aggresomes. Henceforth, the degradation of Tau and its blockage that is associated with various PTMs of Tau would explain the dynamics of Tau degradation or accumulation in AD. Further, unveiling the role of accessory proteins involved in these degradation pathways would help in understanding their loss of function and preventing Tau clearance.